Gynecological surgical approach to a patient with Sneddon’s syndrome - Cura Şahin, Gizem; Sahin, Bugra; Çelik, Fatih (Journal of Surgery and Medicine, 2021)
In this case report, the management of a patient with Sneddon’s syndrome who underwent laparoscopic hysterectomy for menometrorrhagia and multiple leiomyoma uteri is discussed. The clinical management of Sneddon’s syndrome is based on four distinct aspects: Neurological, hematological, dermatological, and psychiatric. Their analysis can be a valuable tool in the preoperative and postoperative monitoring of these patients.